1993
DOI: 10.1093/cvr/27.7.1278
|View full text |Cite
|
Sign up to set email alerts
|

Membrane current changes in left ventricular myocytes isolated from guinea pigs after abdominal aortic coarctation

Abstract: After infrarenal aortic coarctation, action potential duration of left ventricular myocytes is prolonged. This prolongation may be attributed to an increase in calcium current density and a shift of its inactivation variable, together with an increased magnitude and prolonged time course of sodium-calcium exchange current. These current changes are potentially arrhythmogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 0 publications
7
64
0
1
Order By: Relevance
“…The experiments conducted in this study were designed to limit the activation of 'K by using short voltage clamp pulses to 0 mV; other workers have reported that the activation of IK in guinea-pig ventricular myocytes under similar conditions is limited (Matsuura et al 1987;Ryder et al 1993). However, the results of Fig.…”
Section: The Delayed Rectifier Ikmentioning
confidence: 96%
“…The experiments conducted in this study were designed to limit the activation of 'K by using short voltage clamp pulses to 0 mV; other workers have reported that the activation of IK in guinea-pig ventricular myocytes under similar conditions is limited (Matsuura et al 1987;Ryder et al 1993). However, the results of Fig.…”
Section: The Delayed Rectifier Ikmentioning
confidence: 96%
“…Previous studies on left ventricular trabeculae (Meszaros & Levai, 1990, 1992Meszaros, 1992) (Kleiman & Houser, 1988;Scamps et al 1990;Bouron, Potreau & Raymond, 1992;Cerbai, Barbieri, Li & Mugelli, 1994) although in mild (Ryder et al 1993) and moderate (Keung, 1989) hypertrophy, an increase in ICa density has been reported. Only in severe cardiac hypertrophy, in which congestion is present, has ICa density been reported to decrease (Nuss & Houser, 1991; Rossner, 1991;Aiba & Creazzo, 1992;Hatem, Sham & Morad, 1994; LeGrand, Hatem, Deroubaix, Couetil & Coraboeuf, 1994;Ming, Nordin, Sirn & Aronson, 1994).…”
Section: Discussionmentioning
confidence: 83%
“…Single left ventricular myocytes from the rat hearts were obtained according to the method described previously (Ryder, Bryant & Hart, 1993). The cells were stored at room temperature in Dulbecco's modified Eagle's medium with 2 mg/ml Ultraser G (Gibco BRL, Paisley, UK) for up to 8 h.…”
Section: Cell Isolationmentioning
confidence: 99%
“…In right ventricular hypertrophy, Ica density has been reported to decrease by some investigators, 1,5) or be unchanged by others. 9) In left ventricular hypertrophy, Ica density has been reported to decrease, 5) increase, 3,4) or be unchanged. 7,8) Lee, et al 11) has raised a possible comprehensive interpretation of these controversial results, suggesting that the Ica density varied according to the stage of the acquired hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) In contrast to the Ito density, the results for the changes in inward L-type calcium current (Ica) in hypertrophic hearts remain controversial. Some have reported an increase in its density, 3,4) but others a decrease. 1,5,6) Moreover, no changes in its density have been noted.…”
mentioning
confidence: 99%